1986
DOI: 10.1037/0022-3514.51.6.1156
|View full text |Cite
|
Sign up to set email alerts
|

The repulsion hypothesis: On the nondevelopment of relationships.

Abstract: A universal contention in the psychological literature is that attitudinai similarity leads to attraction. I argue that attitudinai similarity does not lead to liking but that dissimilarity does indeed lead to repulsion. Primary attention is given to Byrne's experimental paradigm in which subjects are shown the attitude scale of a stranger that is similar or dissimilar to their own and who are then asked to indicate their attraction to the stranger. Consistently, Byrne and others have found a linear relation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
283
2
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(303 citation statements)
references
References 42 publications
(54 reference statements)
14
283
2
3
Order By: Relevance
“…There is evidence that people assume substantial similarity with other individuals in general (Byrne et al, 1986) and with romantic partners in particular, even when such perceived similarity is not justified by reality (Acitelli et al,1993;Murray et al, 2002). Therefore, receiving information that disconfirms assumed similarity reliably reduces attraction relative to a no information control, whereas information that affirms similarity does not always increase attraction (Rosenbaum, 1986). As discussed, women have been repeatedly shown to actively protect relationships against various threats (e.g., violations of assumed similarity).…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that people assume substantial similarity with other individuals in general (Byrne et al, 1986) and with romantic partners in particular, even when such perceived similarity is not justified by reality (Acitelli et al,1993;Murray et al, 2002). Therefore, receiving information that disconfirms assumed similarity reliably reduces attraction relative to a no information control, whereas information that affirms similarity does not always increase attraction (Rosenbaum, 1986). As discussed, women have been repeatedly shown to actively protect relationships against various threats (e.g., violations of assumed similarity).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, it generates novel predictions regarding possible effects of similarity on attraction. Numerous studies have demonstrated that greater levels of similarity lead to attraction (e.g., Berscheid, 1985;Byrne, 1971;Byrne et al, 1966;Newcomb, 1956; for a review, see Byrne, 1997; although see, Aron, Steele, Kashdan, &Perez, 2006, andRosenbaum, 1986, for other perspectives on the similarity-attraction relationship). From the present perspective, however, this relationship should also depend on the value of low-and high-level construal features associated with the other person.…”
Section: Projectionmentioning
confidence: 99%
“…A second powerful effect is the similarity-attraction effect (or dissimilarity-repulsion effect [Rosenbaum, 1986])-the tendency to be attracted to people as a function of the similarity of their attitudes to your own. In the research on this effect, the experimenter prepares a description of another person, which consists of a list of that person's opinion responses.…”
Section: Some Strong Attitude Ettectsmentioning
confidence: 99%